Financial inclusion, institutional framework and social capital in Latin America (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2025)
The purpose of the study is to determine the effect of institutionality and social capital on financial inclusion in Latin America, in a sample of 16 countries for the period 2011-2021, with four time observations (2011, 2014, 2017 and 2021). Fixed effects and random effects models were estimated, considering the proportion of the population with bank accounts as the dependent variable and banking infrastructure (ATMs and branches) and technology (internet access) as explanatory variables in the first model, to which socioeconomic variables (education and business conditions) were added in a second model, and finally, institutions (governance and personal freedoms) and social capital were incorporated in a third model. The results indicate that, while banking and technological infrastructure have a significant impact on financial inclusion, institutions and social capital do not, although the sign of the relationships is positive, as suggested by the literature.
Keywords: financial inclusion; banking infrastructure; social capital; governance; personal freedoms